Proksemika. Studium z antropologii kulturowej - Hendrykowski, Marek (Przestrzenie Teorii, 2015)
Marek Hendrykowski’s study deals with the semiotics of interpersonal proxemic relationships in today’s world. When analyzing this issue, the author puts forward three research hypotheses. First, interpersonal relationships that are connected with social space are not on the margins of systems of culture, but constitute a very important characteristic of each such system. Secondly, the traditional ways of defining proxemics, which emphasize the existence of interpersonal barriers, present the complex issues related to this field of science of signs and meanings too narrowly and usually in a schematic manner. And thirdly, the profound changes in proxemic relationships that are taking place in the macrosystem of contemporary culture have a major influence on the functioning of culture itself as well as on how individuals, groups and communities participate in this culture. When analyzed in terms of the proxemics of interpersonal relationships, the cultural ecosystem is not an abstract model but an operating system which governs the daily living conditions of individuals, groups and communities.